Treatment of venous thromboembolism in patients with cancer: A network meta-analysis comparing efficacy and safety of anticoagulants. Issue 3 (September 2015) - Posch, Florian; Königsbrügge, Oliver; Zielinski, Christoph; Pabinger, Ingrid; Ay, Cihan
Abstract Introduction Low-molecular-weight heparin (LMWH) and vitamin K antagonists (VKA) are current treatment options for cancer patients suffering from acute venous thromboembolism (VTE). The role of direct-acting oral anticoagulants (DOACs) for the treatment of VTE in cancer patients, particular in comparison with the current standard of care which is LMWH, remains unclear. In this network meta-analysis, we compared the relative efficacy and safety of LMWH, VKA, and DOAC for the treatment of cancer-associated VTE. Methods A pre-specified search protocol identified 10 randomized controlled trials including 3242 cancer patients. Relative risks (RR) of recurrent VTE (efficacy) and major bleeding (safety) were analyzed using a random-effects meta-regression model. Results LMWH emerged as significantly superior to VKA with respect to risk reduction of recurrent VTE (RR = 0.60, 95%CI:0.45-0.79, p < 0.001), and its safety was comparable to VKA (RR = 1.08, 95%CI:0.70-1.66, p = 0.74). For the DOAC vs. VKA efficacy and safety comparison, the relative risk estimates were in favor of DOAC, but had confidence intervals that still included equivalence (RR for recurrent VTE = 0.65, 95%CI:0.38-1.09, p = 0.10; RR for major bleeding = 0.72, 95%CI:0.39-1.37, p = 0.32). In the indirect network comparison between DOAC and LMWH, the results indicated comparable efficacy (RR = 1.08, 95%CI:0.59-1.95, p = 0.81), and a non-significant relative risk towards improved safety with DOAC (RR = 0.67, 95%CI:0.31-1.46, p = 0.31). The results prevailed after adjusting for different risk of recurrent VTE and major bleeding between LMWH vs. VKA and DOAC vs. VKA studies. Conclusion The efficacy and safety of LMWH and DOACs for the treatment of VTE in cancer patients may be comparable. Funding Austrian Science Fund (FWF-SFB-54)